Mangrove untuk Ketahanan Iklim berdasarkan Indeks Kerentanan Pesisir, Penerapan di Mempawah, Kalimantan Barat: Mangrove untuk Ketahanan Iklim berdasarkan Indeks Kerentanan Pesisir - Eleven Saputra; Permata Mei Kartika; Harefa, Meilinda Suriani (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2024)
Coastal areas are particularly vulnerable to climate change. The primary objective of this study is to use the Geographic Information System (GIS) approach to assess the level of vulnerability in the coastal area of Mempawah Regency, West Kalimantan, Indonesia, by utilizing the Coastal Vulnerability Index (CVI) and analyzing the role of mangrove land cover in explaining the coastal vulnerability based on land cover characteristics. From 41 surveyed grids, a substantial 65.83% are classified under the category of very low vulnerability, while 34.14% fall within the range of low vulnerability, in Mempawah. The validation of the mangroves' role as a defense mechanism in mitigating climate phenomena within coastal areas was validated through various approaches such as Normalized Difference Vegetation Index (NDVI) and land cover